Rethinking drug use in sport: why the war will never be won - Stewart, Bob (Routledge research in sport, culture and society, 2014)
"Drug free sport is an unattainable aspiration. In this critical, paradigm-shifting reappraisal of contemporary drug policy in sport, Bob Stewart and Aaron Smith argue that drug use in sport is an inexorable consequence of the nature, structure and culture of sport itself. By de-mythologising and de-moralising the assumptions that prop up current drug management controls, and re-emphasising the importance of the long-term well being and civil rights of the athlete, they offer a powerful argument for creating a legitimate space for drug use in sport. The book offers a broad ranging overview of the social and commercial pressures impelling drug use, and maps the full historical and social extent of the problem. With policy analysis at the centre of the discussion, the book explores the complete range of social, management, policy, scientific, technological and health issues around drugs in sport, highlighting the irresolvable tension between the zero-tolerance model as advanced by WADA and the harm-reduction approach adopted by drug education and treatment agencies. While there are no simple solutions, as long as drugs use is endemic in wider society the authors argue that a more nuanced and progressive approach is required in order to safeguard and protect the health, social liberty and best interests of athletes and sports people, as well as the value of sport itself"--